The effect of extraction methods towards antioxidant activity of ethanol extract of Picria fel-terrae Lour. Herbs. Issue 1 (1st December 2022) - Dalimunthe, A; Pertiwi, D; Muhmmad, M; Kaban, V E; Nasri, N; Satria, D
Abstract: Antioxidants are molecules that can inhibit or prevent the oxidation reactions of other molecules that generate free radicals. Antioxidants can be synthesized in the body (endogenous) or obtained from food intake (exogenous). Modern pharmacological investigations show that the extract of Picria fel-terrae Lour. Herbs. Effective as an antioxidant because of the high content of flavonoids and phenols. This study aims to analyze the antioxidant activity, total phenol content and total flavonoid content in ethanol extract (EE). The powder was extracted by Soxhletation, percolation and reflux method with absolute ethanol. Antioxidant activity was analyzed by 1, 1-diphenyl-2-picrylhydrazyl (DPPH), FRAP, ABTS and CUPRAC. Total phenol content was measured using the Folin-Ciocalteau method and total flavonoid content was measured using AlCl3 reagent using colorimetric method. The best antioxidant activity and the highest total phenolic content were indicated by the soxhlet extraction method with IC50 23.52 ± 0.17 g/mL and 160.77 ± 0.95 mg GAE/g, and the highest total flavonoid content was indicated by the reflux method (1.08 ± 0. 02 mg QE/g). In conclusion, the ethanolic extract of Picria fel-terrae Lour. Herbs Lour with reflux extraction method can be further developed as an antioxidant.